Ant communities and Solidago plant invasion: Environmental properties and food sources. Issue 3 (23rd February 2018) - Trigos‐Peral, Gema; Casacci, Luca P.; ŚlipiŃski, Piotr; GrzeŚ, Irena M.; MoroŃ, Dawid; Babik, Hanna; Witek, Magdalena
Abstract: The invasion of Solidago is one of the main threats to the biodiversity of natural meadows, leading to changes in animal and plant communities, as well as soil features. We compared effects of soil microclimatic conditions (temperature and moisture) and the availability of potential protein sources (dry mass of epigean invertebrates) on ants between meadows invaded by Solidago altissima and S. canadensis and those uninvaded. Our results showed that the ant communities were different between the uninvaded and invaded meadows, with reduction of ant abundance and species richness in the latter. Myrmica spp. were abundant in the uninvaded meadows, whereas Lasius niger was the dominant species in the invaded ones. We found that the lower moisture negatively influenced the abundance of Myrmica species in the Solidago ‐invaded meadows. Moreover, the epigean invertebrate dry mass, as an estimation of the availability of protein sources, varied between the two types of meadows, with a higher abundance in the uninvaded ones. The abundance of Myrmica ants with narrower ecological requirements showed a positive correlation with the invertebrate biomass in the invaded meadows. In contrast, the abundance of L. niger with broad ecological requirements was negatively correlated with the invertebrate biomass in the invaded meadows, possibly as a strategy to reduce interspecific competition. Our study showed that the invasion of Solidago plants caused changes in the abundance and species composition of ant communities through modification in microhabitat conditions, that is, decreasing soil moisture, reducing biomass and changing distribution of prey invertebrates. Abstract : Solidago invasion decreases the soil moisture and the epigean invertebrate biomass, that is, the availability of protein sources for ants. These two factors seem to affect the ant community structure and species composition in Solidago ‐invaded meadows.